Convergence acceleration of Fourier series revisited - Nersessian, Anry (Armenian Journal of Mathematics, 2011)
A generalization of the Krylov-Eckhoff method is investigated for removing of the classical Gibbs phenomenon. Convergence acceleration scheme for Fourier expansions of piecewise smooth functions is derived. Numerical results are presented and discussed.